Xeroderma pigmentosum. Case presentation. - Damaris Díaz Leonard; Arelis Herrera Alonso; Magdalena Vigera Fajardo (Medisur)
Twelve years old patient (YGS), female, white, of rural origin; with history of facial and truncal bullae since the age of eight months when exposed to the sun light. It was first diagnosed as solar dermatitis. At the age of 6 it was assessed as xeroderma pigmentosum. This diagnosis was confirmed at the age of 10 by the histopathology department and reassessed by the National Reference Centre. For the infrequency of this disease, a bibliographic revision was carried out to make a report for this case presentation.